The alleviation of poverty under structural adjustment - Demery, Lionel (World Bank e-Library., 1987)
This study has identified a number of examples in which concerns about the alleviation of poverty have been given some practical expression in adjustment programs. Because most of these examples are of very recent origin, it is difficult to assess how effective they have been in helping the poor. First, one striking feature of the illustrations compiled is that they are invariably orderly or planned structural adjustment programs that have often been implemented with Bank assistance (Bolivia, Cote d'Ivoire, The Gambia, Indonesia, Jamaica, and Thailand). Second, income distributions will inevitably change during adjustment. These changes are the principal incentives for resource reallocation, and without them the objectives of adjustment will not be realized. Third, the study highlights the advantages of interventions that increase the primary income claims of the poor. Finally, adjustment can act as a catalyst for policymakers to examine carefully the costs and benefits of their programs for the poor.